Political Disputes in Brazilian Rock in Times of Bolsonarism: demystifying the Progressive Inherence of Rock from Douglas Kellner (Orfeu, 2023)
This article seeks to demonstrate the political disputes that permeated the Brazilian rock scene during the Bolsonarism period, in order to demystify the idea that rock is inherently progressive. To do so, we base ourselves on the reflections of the philosopher Douglas Kellner, especially on his work on media culture and its dichot-omies. By adopting Kellner’s perspective, the research argues that Brazilian rock, as well as other forms of cultural expression, is not intrinsically progressive or conservative, but rather a field of dispute where different ideologies and interests manifest themselves. Through the analysis of these political disputes, the study contributes to a more complex and nuanced understand-ing of the role of rock music in the Brazilian sociopolitical context.
Keywords: Brazilian rock; bolsonarism; policy